Phase II Trial of Pre-Irradiation and Concurrent Temozolomide in Patients with Newly Diagnosed Anaplastic Oligodendrogliomas and Mixed Anaplastic Oligoastrocytomas: Long Term Results of RTOG BR0131 - Vogelbaum, Michael A. (J Neurooncol, 2015)
BACKGROUND: We report on the long-term results of a phase II study of pre-irradiation temozolomide followed by concurrent temozolomide and radiotherapy (RT) in patients with newly diagnosed anaplastic oligodendroglioma (AO) and mixed anaplastic oligoastrocytoma (MOA). METHODS: Pre-RT temozolomide was given for up to 6 cycles. RT with concurrent temozolomide was administered to patients with less than a complete radiographic response. RESULTS: Forty eligible patients were entered and 32 completed protocol treatment. With a median follow-up time of 8.7 years (range: 1.1 to 10.1), median progression-free survival (PFS) is 5.8 years (95% C.I. 2.0, NR) and median overall survival (OS) has not been reached (5.9, NR). 1p/19q data are available in 37 cases; 23 tumors had codeletion while 14 tumors had no loss or loss of only 1p or 19q (non-codeleted). In codeleted patients, 9 patients have progressed and 4 have died; neither median PFS nor OS have been reached and two patients who received only pre-RT temozolomide and no RT have remained progression-free for over 7 years. 3-year PFS and 6-year OS are 78% (95% CI: 61-95%) and 83% (95% CI: 67-98%), respectively. Codeleted patients show a trend towards improved 6-year survival when compared to the codeleted procarbazine/CCNU/vincristrine (PCV) and RT cohort in RTOG 9402 (67%, 95% CI:55-79%). For non-codeleted patients, median PFS and OS are 1.3 and 5.8 years, respectively. CONCLUSIONS: These updated results suggest that the regimen of dose intense, pre-RT temozolomide followed by concurrent RT/temozolomide has significant activity, particularly in patients with 1p/19q codeleted AOs and MAOs.